DISTRIBUTION AND FUNCTIONAL ROLE OF AMPHIBIANS IN ROZHNIATIV DISTRICT - Цимбалюк, Василь; Микитин, Тетяна (SWorldJournal, 2025)
This study investigated the species composition, functional role, and anthropogenic threats to the batrachofauna (amphibians) in the Rozhniativ district of Ivano-Frankivsk region, a representative Carpathian foothill area. Field surveys were conducted thr